Taxonomic clarification of the Eumicrotremus asperrimus species complex (Teleostei: Cyclopteridae) in the eastern North Pacific - Stevenson, Duane E.; Mecklenburg, Catherine W.; Kai, Yoshiaki (Zootaxa, 2017)
The Eumicrotremus asperrimus species complex includes three nominal species from the eastern North Pacific and Bering Sea: Eumicrotremus gyrinops (Garman 1892); Eumicrotremus muticus (Gilbert 1896); and Eumicrotremus phrynoides Gilbert & Burke 1912. These species have been distinguished from each other primarily on the basis of the strength and coverage of bony tubercles on the head and body. However, several recent genetic studies have cast doubt on the utility of bony tubercles for diagnosing species-level differences among cyclopterids, and a recent genetic study of the E. asperrimus species complex indicated that population structure is not correlated with tubercle development. Here we present additional evidence from the mitochondrial COI gene indicating that there is little genetic structure within a sample of specimens from the eastern North Pacific and Bering Sea with a wide range of tubercle development. We also examine several lines of morphological evidence, including meristic and morphometric data and osteology, and conclude that the three nominal species described from the eastern North Pacific represent a single polymorphic species. We present a redescription of Eumicrotremus gyrinops (Garman), the oldest of the three nominal species, recognizing the other two nominal species of the Eumicrotremus asperrimus species complex described from the eastern North Pacific as junior synonyms. Individuals of this highly polymorphic species may be covered in large bony tubercles, or sparsely covered in small tubercles, or may have no evidence of tubercles at all. There is clear evidence of sexual dimorphism, as males tend to have fewer and smaller tubercles than females, and all large specimens (> 58 mm SL) are females. Both males and smaller females may lack any evidence of tubercles.